INTERRELATIONSHIP BETWEEN SELF-MANAGEMENT OF BIOPSYCHOSOCIAL DEVELOPMENT OF STUDENT’S PERSONALITY AND HEALTH HABITS. THEORETICAL ASPECT - Erdmane, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Until now, there has been done little research on the purposeful biopsychosocial development of student personality in Latvia. Also, in pedagogical science there has been little done on the formation of balanced development self-management skills in humans. Each person's biopsychosocial development is in harmony with its health or lifestyle habits. The quality of student life and studies depends on their health which is affected by health habits. Their formation is closely linked to the formation of biopsychosocial development self-management skills in students. The objective of this paper is to analyse the interrelationship between personality biopsychosocial development self-management skills and health habits in students. The paper discovers the nature of biopsychosocial development skill self-management in relation with the formation of health habits in students. In the analysis of the interrelationship between development self-management skills and health habits there have been found the main factors which affect both skill and habit formation.The student biopsychosocial development model has been developed based on American psychiatrist George Engel's theoretical modelling. The principles of balanced biopsychosocial development self-management are based on discoveries in papers on humanpedagogy by Professor A.Spona. The paper looks at the awareness of necessity of student self-development and purposeful self-development in action. The interrelationship between purposeful biopsychosocial development self-management and health habits forms foundation for student attitude formation against themselves, other people, as well as surrounding environment. The results of balanced biopsychosocial development in students manifest together with health habits.